ANALISIS KELAYAKAN INDUSTRI RUMAHAN PAKAN IKAN DI DESA KOTO TIBUN KECAMATAN KAMPAR - , Ufira Isbah, Arif Putra Nistob Mendrofa , Eriyati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the feasibility of a fish feed home industry in Koto Tibun Village, Kampar District, both non-financially and financially. The types of data used are primary data and secondary data. Primary data was obtained directly from the respondents while secondary data was obtained from government agencies. The analytical method used is descriptive analysis on non-financial aspects, namely market aspects, technical and technological aspects, socio-economic aspects, legal aspects. While quantitative analysis to analyze the financial aspects, namely Net Present Value (NPV), Benefit Cost Ratio (B/C Ratio), Internal Rate of Return (IRR) and Payback Period (PP). The results showed that on the non-financial aspect, the fish feed home industry in Koto Tibun, Kampar District, had met the criteria so that it was feasible to run and develop.  Keywords : Business Feasibility, Fish Feed Home Industry, NPV, B/C Ratio, IRR, PP.